2003
DOI: 10.1002/smi.980
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an intensive stress intervention workshop for senior managers

Abstract: This study investigates the efficacy of an intensive, integrated approach to stress reduction and coping enhancement directed towards an educated, upper level management population. Ninety‐five US governmental senior managers participated in a 35‐h stress management retreat held over a 3.5‐day period. The retreat combined didactic and experiential activities that were designed to increase participants' knowledge of stress liabilities and coping skills. Participants were encouraged to make positive lifestyle ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Participants reported such tactics as identifying an adviser who was well-versed in the issue of women in STEM contexts, forming study groups with other students, and taking courses with friends. As previous research has shown (Horan, 2002;Veach, Rahe, & Tolles, 2003), coping is a trainable skill; counselors can coach students to help them to have a positive STEM experience.…”
Section: Implications For School and Career Counselorsmentioning
confidence: 91%
“…Participants reported such tactics as identifying an adviser who was well-versed in the issue of women in STEM contexts, forming study groups with other students, and taking courses with friends. As previous research has shown (Horan, 2002;Veach, Rahe, & Tolles, 2003), coping is a trainable skill; counselors can coach students to help them to have a positive STEM experience.…”
Section: Implications For School and Career Counselorsmentioning
confidence: 91%
“…Stress management programmes from different theoretical foundations and implementation styles have been found to be effective in reducing stress or improving coping skills for worksite employees (van Dierendonck, Garssen, & Visser, 2005;Edimansyah, Rusli, & Naing, 2008;Lucini, Riva, Pizzinelli, & Pagani, 2007;Peters & Carlson, 1999;Shimazu, Umanodan, & Schaufeli, 2006;Veach, Rahe, Tolles & Newhall, 2003;Zolnierczyk-Zreda, 2002). However, detailed written description of the implementation and delivery methods of stress management programmes are often unavailable, thereby making it challenging to further develop evidence-based stress reduction interventions, which are specific to worksites and are based on prior evidence-based outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…51,52 Furthermore, our results showed that opportunities to get help from work colleagues were associated with more symptoms of burnout for both first-line and middle managers. Research has shown that supportive relations within the workplace can be problematic for managers, 53,54 and may explain why help from colleagues within the workplace was related to more symptoms of burnout.…”
mentioning
confidence: 99%